EFFECT OF SAND MINING ACTIVITY ON THE SEDIMENT CONTROL SYSTEM (A CASE STUDY OF SOMBE-LEWARA RIVER, DONGGALA, INDONESIA) - Y. A. Bawias (Journal of the Civil Engineering Forum, 2012)
Sombe-Lewara River is a tributary of Palu River which lies at the most downstream part of Palu River which has 112.38 Km2 of catchment area and 28.11 Km of river length. Sombe-Lewara River comprises three reaches, i.e. Sombe River, Lewara River, and Sombe-Lewara River. In order to control the debris flow disaster, six sediment control structures have been built in Sombe River and another two were built in Lewara River. The sand mining activity in Sombe-Lewara River has caused river degradation and to some extent damaged sediment control structures. In order to prevent the river from further degradation and decrease in environment condition, a proper sediment management is therefore considered necessary.  This paper illustrates the sediment balance analysis which applies the empirical formula of sediment supply at the upstream of sediment control structure and storage characteristics of sediment control structures, the initiation of debris flow occurrence and the sediment volume controlled by sediment control structures. The sediment balance was studied based on the sediment flow within the period of 2000 through 2009, at the existing infrastructures and the further development of sediment control structures. The results show that at 10 mm rainfall depth over the catchment, the average annual sediment supply at Somber River and Lewara River was found to be approximately 240,195 m3 and 112,500 m3 respectively. Within the above period, the sediment volume passing through control point 1 was approximately 105,890 m3. Furthermore, the sand mining activity at Sombe-Lewara River has caused severe river degradation and damage on the existing sediment control structures. Keywords: Sediment balance, sediment control structures, sand mining.